Evaluation of sodium orthovanadate as a radioprotective agent under total-body irradiation and partial-body irradiation conditions in mice. (2nd September 2021) - Nishiyama, Yuichi; Morita, Akinori; Wang, Bing; Sakai, Takuma; Ramadhani, Dwi; Satoh, Hidetoshi; Tanaka, Kaoru; Sasatani, Megumi; Ochi, Shintaro; Tominaga, Masahide; Ikushima, Hitoshi; Ueno, Junji; et al.
Abstract: Purpose: Our previous study indicated that sodium orthovanadate (vanadate), a strong inhibitor of p53, effectively suppressed the lethality from the hematopoietic (HP) and gastrointestinal (GI) syndromes after 12 Gy total-body irradiation (TBI) in mice. This conclusion, however, was inconsistent with the fact that p53 plays a radioprotective role in the intestinal epithelium. The death after TBI of around 12 Gy was attributed to a combined effect of HP and GI syndromes. To verify the effect from prophylactic administration of p53 inhibitor on protection of HP and GI syndromes, in this study, the radioprotective effects from vanadate were investigated in TBI and lower half-body irradiation (partial-body irradiation: PBI) mouse models. Methods: Female ICR mice were given a single injection of vanadate or vehicle, followed by a lethal dose of TBI or PBI. Radioprotective effects of vanadate against the irradiations were evaluated by analyzing survival rate, body weight, hematopoietic parameters, and histological changes in the bone marrow and intestinal epithelium. Results: TBI-induced HP syndrome was effectively suppressed by vanadate treatment. After TBI, the vanadate-treated mice retained better bone marrow cellularity and showed markedly higher survival rate compared to the vehicle-treated animals. In contrast, vanadate did not relieve loss of intestinal crypts and failed to rescue mice from GI death after PBI. Conclusion: Vanadate is a p53 inhibitor that has been shown to be beneficial as a radiation protective agent against HP but was not effective in protecting against acute GI radiation injury.